Upaya Meningkatkan Hasil Belajar IPS Ekonomi dengan Menggunakan Metode Inkuiri pada Peserta Didik Kelas VIII SMP Muhammadiyah Palangka Raya - Andi Admaja; Bulkani Bulkani (Neraca: Jurnal Pendidikan Ekonomi, 2018)
This study aims to determine learning activities and increase learning outcomes. The subjects in this study were all students of class VIII.5 of Muhammadiyah Middle School in Palangka Raya, which numbered 23 students. The method in this study uses the Classroom Action Research (CAR) method. The results of the survey show that: (1) Students are more active in the learning process so that students can understand the material presented properly. This can be seen from the scores of social studies learning activities of students in the first cycle, there were 12 students who scored 21, and in the second cycle, there were 23 students who scored 21: (2) the use of inquiry methods could improve learning outcomes. In the first cycle of 16 students, the average learning outcome was 61.30 with a percentage of 69.56%, and in the second cycle of 23 students, the average learning outcomes increased to 75.65 with a rate of 95.65%. There was an increase of 26.09% from the period I to II.